View of statins as antimicrobials in cardiovascular risk modification. (12th March 2014) - Kozarov, Emil; Padro, Teresa; Badimon, Lina
Abstract: Atherosclerosis is a complex arterial pathological development underlying heart attack and stroke and a leading cause of death in developed and now also in developing countries. The primary processes that lead to the inflammatory lipid-laden proliferative lesion, obstructing the blood flow, and referred to as atherosclerotic plaque are dyslipidaemia and inflammation. Here, we will review one of the most efficient classes of drugs indicated for management of cardiovascular disease (CVD), statins. We will assess their pleiotropic effects that emerged from CVD applications, focusing this review specifically on plausible antimicrobial activity. Only recently gaining strength, the recognition of possible antibacterial activity may extend the statin applicability for vascular as well as to other critical inflammatory conditions.